SISTEM PENDUKUNG KEPUTUSAN DIAGNOSA PENYAKIT PARU-PARU - mhd ali (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2019)
A decision support system for diagnosing lung disease by inserting sketches of x-ray images that have been copied into the decision support system for lung disease diagnosis and symptoms of the disease to be diagnosed at a later stage so that the type of disease is known. The purpose of this system is to support the decision to diagnose lung disease where there are input symptoms of the disease or scanned images, to determine the level or level of illness suffered by the patient or ordinary person. This program is run by using hardware (hardware) that has minimal specifications are as follows Intel Pentium II 200 Mhz Processor, 64 MB Memory, 10 GB Hard Drive, 1 MB VGA card, Monitor with a resolution of 800  600 pixels, Keyboard and Mouse; Whereas the software used to run this application is the MS-Windows 98 or MS-Windows NT / 2000 / XP operating system environment. Steps for making this system include: identifying problems and needs, collecting and selecting data that will be used as a complement, studying and discussing the material obtained about the decision system for diagnosing lung disease along with forward chaining and production rules, designing interfaces with using Microsoft Visual Basic 6.0. and designing databases with Microsoft SQL Server 2000, making decision support systems for diagnosing lung disease, and testing and improving the systems made.